Accelerating Crystallization of Open Organic Materials by Poly(ionic liquid)s. (1st October 2020) - Zhang, Su‐Yun; Miao, Han; Zhang, He‐min; Zhou, Jun‐Hao; Zhuang, Qiang; Zeng, Yu‐Jia; Gao, Zhiming; Yuan, Jiayin; Sun, Jian‐Ke
Abstract: The capability to significantly shorten the synthetic period of a broad spectrum of open organic materials presents an enticing prospect for materials processing and applications. Herein we discovered 1, 2, 4‐triazolium poly(ionic liquid)s (PILs) could serve as a universal additive to accelerate by at least one order of magnitude the growth rate of representative imine‐linked crystalline open organics, including organic cages, covalent organic frameworks (COFs), and macrocycles. This phenomenon results from the active C5‐protons in poly(1, 2, 4‐triazolium)s that catalyze the formation of imine bonds, and the simultaneous salting‐out effect (induced precipitation by decreasing solubility) that PILs exert on these crystallizing species. Abstract : 1, 2, 4‐Triazolium poly(ionic liquid) (PIL) is an additive to accelerate by at least one order of magnitude the crystallization rate of imine‐linked crystalline open organics (organic cages, covalent organic frameworks (COFs), and macrocycles). This acceleration effect stems from the active C5 protons in polytriazolium that catalyze formation of imine bonds and the salting‐out effect of PILs on these crystallizing species.